FROM READINESS TO DESIGN: MAPPING PRE-SERVICE CHEMISTRY TEACHER’S INCLUSIVE COMPETENCIES WITH CHARLOTTE DANIELSON’S FRAMEWORK - ‘Azmi, Madah Ikrimatul; Suprihatiningrum, Jamil; Wulayalin, Khafifah Aulia (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
This study examines the inclusive teaching readiness of pre-service chemistry teachers using Charlotte Danielson’s Framework for Teaching (FfT) as an analytic lens and as an entry point to Educational Design Research (EDR). Fifty participants from six Indonesian state universities were surveyed with a 22-indicator Likert instrument adapted from the FfT. The instrument showed good internal consistency (α = .87). Descriptive statistics and non-parametric tests were used to compare domains and explore variance. Results indicate high competencies in Planning & Preparation, Classroom Environment, and Instruction, while Professional Responsibility shows comparatively lower means and greater dispersion. Weakest indicators include adaptive assessment, inclusive/multimodal communication, and professionalism, suggesting both curricular gaps and unequal access to clinical experiences. Potential ceiling effects in planning signal the need for more sensitive, authentic indicators (e.g., project-based assessment across representations). We translate these findings into EDR design principles prioritizing (1) adaptive assessment, (2) multimodal communication, (3) mentoring and professional learning communities, and (4) accessibility audits for laboratory spaces. The study formulates EDR design principles emphasizing adaptive assessment, multimodal strategies, mentoring networks, and accessibility audits. Overall, this research operationalizes the Charlotte Danielson’s FfT in inclusive chemistry education, linking empirical measurement to practical design solutions and offering implications for curriculum reform and iterative EDR-based model development.